The Relationship Between Abraham Maslow's Theory of Learning Motivation and the Learning Motivation of FKIP Students of Nusa Cendana University - Salmon Runesi; Al Ihzan Tajuddin; Ronald Dwi Ardian Fufu; Yudabbirul Arif (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The goal is that students have motivation that is in line with the principles of learning motivation and can participate in every learning activity in theory and practice. The design used in the implementation of this research is Ex post facto. The method used is non-experimental quantitative. The instrument used in the form of a questionnaire aimed at collecting data on Abraham Maslow's motivation theory with the learning motivation of Physical Education Students consists of five aspects namely physiological needs, security needs, social needs, self-esteem needs, self-actualization needs which are independent variables or those that affect two aspects, namely learning activities in the classroom or the field and independent activities of students which are dependent or influenced variables. The sample in this study used simple random sampling. The research sample selected as many as 35 students of Semester II, IV and VI. The results of Abraham Maslow's theory of learning motivation with learning motivation of 35 Penjaskesrek students are in moderate qualifications with an average score of 162, in the interval (157 – 164), and the learning motivation of Penjaskesrek students lies in moderate qualifications with an average score. the average is 130, is in the interval (126 – 132). Thus, there is a significant influence between Abraham Maslow's theory of learning motivation and the learning motivation of Penjaskesrek FKIP students, Nusa Cendana University, Kupang in 2020. It appears that r count (0.609) is greater than r table (0.344), 0.609 > 0.344. The results showed that there was a positive and quite strong influence so that there was a relationship between Abraham Maslow's theory of learning motivation and the learning motivation of Penjaskesrek FKIP students, Nusa Cendana University, Kupang in 2022 of 0.609.